2021
DOI: 10.1186/s10033-021-00664-2
|View full text |Cite
|
Sign up to set email alerts
|

Sheet Bulk Forming of Thin-Walled Components with External Gearing through Upsetting Using Controllable Deformation Zone Method

Abstract: Sheet-bulk metal forming (SBMF) is a promising process for manufacturing complex sheet components with functional elements. In this study, the entire forming process for a typical thin-walled component with external gearing is investigated, including sheet forming and bulk forming processes. Deep drawn cups are prepared during sheet forming; subsequently, upsetting is performed on the sidewall to form external gearing. The upsetting method performed is known as upsetting with a controllable deformation zone (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The technique could be employed to forming flanges both on product end and in its centre [19]. It could also be used as a finishing operation in upsetting cups with increased wall thickness [20] or components with external gearing [21]. A study [22] showed that the forming force was nearly constant during the process.…”
Section: Introductionmentioning
confidence: 99%
“…The technique could be employed to forming flanges both on product end and in its centre [19]. It could also be used as a finishing operation in upsetting cups with increased wall thickness [20] or components with external gearing [21]. A study [22] showed that the forming force was nearly constant during the process.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2019) applied the flow model in metal cutting to cold forging of tubular products. As reported by Zhuang et al (2019Zhuang et al ( , 2021 and Hsu et al (2021), the controllable deformation zone method could be adopted to manufacture thin-walled components with gear and flange features, and copper heat spreader with high quality. Wang et al (2013) proposed a new process, namely compressiondrawing method, to manufacture central bosses on the bottom of a cup with a lower forming load, which may provide a valuable solution for the fabrication of local features such as gears and small corners.…”
Section: Introductionmentioning
confidence: 99%